2010
DOI: 10.1097/jto.0b013e3181dcf920
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Lymphatic Involvement in Patients Having Pulmonary Metastasectomy: Incidence and the Effect on Prognosis

Abstract: Mediastinal and hilar lymph node involvement are rarely reported in the literature concerning pulmonary metastasectomy. The first problem is to determine with accuracy the incidence and location of thoracic lymph node involvement in patients with lung metastases. Determination of the impact on survival of this type of lymphatic spread may contribute to assessing whether metastatic nodal disease identified preoperatively is an absolute contraindication to metastasectomy. Systematic mediastinal lymph node dissec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 11 publications
0
25
0
4
Order By: Relevance
“…According to some studies an improvement in long-term survival is also possible, e.g. in patients with preoperatively unidentifi ed affl iction of mediastinal lymphatic nodes which may be up to 14% according to Loehe (3,16,27,32). In our group, the tumor infi ltration in regional lymphatic nodes was not preoperatively expected in any of our 8 patients (9.2 % of the whole group, 15.4 % of the performed collections).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…According to some studies an improvement in long-term survival is also possible, e.g. in patients with preoperatively unidentifi ed affl iction of mediastinal lymphatic nodes which may be up to 14% according to Loehe (3,16,27,32). In our group, the tumor infi ltration in regional lymphatic nodes was not preoperatively expected in any of our 8 patients (9.2 % of the whole group, 15.4 % of the performed collections).…”
Section: Discussionmentioning
confidence: 72%
“…The frequency of affl iction of hilar and mediastinal lymphatic nodes by dissemination of cancer is described within a range of 8 to 33 % in pulmonary metastases with a demonstrably worse survival (27,30,31,32). The benefi t of SMLA in pulmonary metastasectomy is currently under investigation, nevertheless it is largely recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actuellement, la place du curage ganglionnaire pour les métastases de cancers colorectaux tend à se généraliser et devient de moins en moins controversée dans cette indication. Durant ces 15 dernières années, trois grandes méta-analyses ont été rapportées sur la prise en charge chirurgicale des métastases pulmonaires, notamment liées au cancer colorectal [1,[32][33][34][35].…”
Section: Place Du Curage Ganglionnaireunclassified
“…The results obtained in this study were slightly higher than those reported in the literature, and this can be explained as follows: The European Society of Thoracic Surgeons suggests determining whether the patients who underwent pulmonary metastasectomy had lymph node metastases before undergoing surgery. The incidence of lymph node presence in patients undergoing pulmonary metastasectomy was approximately 20% (21). Applying mediastinoscopy to patients is unusual before performing this operation (22).…”
Section: N (%)mentioning
confidence: 99%